Homologous recombination of monkey alpha-satellite repeats in an in vitro simian virus 40 replication system: possible association of recombination with DNA replication. - Kawasaki, I (1994)
To study homologous recombination between repeated sequences in an in vitro simian virus 40 (SV40) replication system, we constructed a series of substrate DNAs that contain two identical fragments of monkey alpha-satellite repeats. Together with the SV40-pBR322 composite vector encoding Apr and Kmr, the DNAs also contain the Escherichia coli galactokinase gene (galK) positioned between two alpha-satellite fragments. The alpha-satellite sequence used consists of multiple units of tandem 172-bp sequences which differ by microheterogeneity. The substrate DNAs were incubated in an in vitro SV40 DNA replication system and used to transform the E. coli galK strain DH10B after digestion with DpnI. The number of E. coli galK Apr Kmr colonies which contain recombinant DNAs were determined, and their structures were analyzed. Products of equal and unequal crossovers between identical 172-bp sequences and between similar but not identical (homeologous) 172-bp sequences, respectively, were detected, although those of the equal crossover were predominant among all of the galK mutant recombinants. Similar products were also observed in the in vivo experiments with COS1 cells. The in vitro experiments showed that these recombinations were dependent on the presence of both the SV40 origin of DNA replication and SV40 large T antigen. Most of the recombinant DNAs were generated from newly synthesized DpnI-resistant DNAs. These results suggest that the homologous recombination observed in this SV40 system is associated with DNA replication and is suppressed by mismatches in heteroduplexes formed between similar but not identical sequences.